PENERAPAN KONSEP SOSIOLOGIS DALAM PENDIDIKAN DASAR - Ricky Gustiawan; Neviyarni; Irda Murni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The aim of this study is to find out the philosophical foundation system in applying sociological concepts in the basic education environment. The research method used in this research is literature study which relies on bibliographic sources from books and articles in scientific journals related to the subject matter, reading data with the thoughts of experts with a constructive and interpretive approach. The results of research from the results of a literature study to be able to carry out the Application of Sociological Concepts in Basic Education require careful preparation to run as the concept of education in carrying out its role which must have sociological foundational implications in education as well as self-development through a sociological basis which is also required to make the latest breakthroughs in the process of curriculum innovation or what is often known as curriculum revision in order to significantly adjust the philosophical foundations and accuracy in applying the sociological foundations in the basic education environment.